2018
DOI: 10.11648/j.ijfsb.20180302.13
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study on the Chemical Composition and Amino Acid Profile of Periwinkle and Rock Snail Meat Powders

Abstract: For the present study, edible parts (meat) from freshly harvested Tympanotonus fuscatus, Pachymelania aurita and Thais coronata were processed into powders and analyzed for proximate composition, amino acid profile and mineral content. The mean values obtained were compared with each other. Results showed that all the parameters determined varied among the three gastropod species. Powders prepared from the three species had high protein and low fat contents. The protein content ranged from 41.51% for T. fuscat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(25 citation statements)
references
References 10 publications
5
11
8
1
Order By: Relevance
“…The procedure described by Inyang et al (2018) and Kumolu-Johnson et al (2010) with slight modifications were adopted in processing the FHP. The length of the periwinkles (with the shell) were within the range of 2.5 -4.0 cm; the weights were between 3.70 -5.30 g. Thorough washing of the whole body of the periwinkles was carried out using potable water in order to remove mud and other foreign materials adhered to the body.…”
Section: Processing Of Periwinklementioning
confidence: 99%
See 3 more Smart Citations
“…The procedure described by Inyang et al (2018) and Kumolu-Johnson et al (2010) with slight modifications were adopted in processing the FHP. The length of the periwinkles (with the shell) were within the range of 2.5 -4.0 cm; the weights were between 3.70 -5.30 g. Thorough washing of the whole body of the periwinkles was carried out using potable water in order to remove mud and other foreign materials adhered to the body.…”
Section: Processing Of Periwinklementioning
confidence: 99%
“…Periwinkle meat is a cheap source of animal protein to many poor families in Nigeria when compared with other sources such as meat, fish, egg, chicken and meat (Ogungbenle and Omowole, 2012;Johnnie et al, 2020). According to Inyang et al (2018), seafood which include periwinkle offers consumers superior quality protein than what is obtainable in meat and poultry. A study carried out by Ogungbenle and Omowole (2012) revealed that periwinkle (Tympanotonus fuscatus var.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Awareness of the nutritional composition, accessibility, and low cost of periwinkle meat is the major reason for high market demand. Both periwinkle and rock snail also command high market values in Akwa Ibom State, Nigeria 19 . The activities surrounding the shellfish value chain, which includes collection, marketing, and processing, form an important economic activity among the people living in the coastal region 20 .…”
Section: Introductionmentioning
confidence: 99%